A luminescent material with enhanced SrAl2O4-based stress luminescence and photoluminescence and a preparation method thereof

By doping Eu and Dy into strontium aluminate and adding B4C, SrAl2O4-based stress luminescence and photoluminescence materials are prepared, which solves the problem of insufficient brightness of existing strontium aluminate phosphors and achieves high-brightness and high-sensitivity stress luminescence effects. It is suitable for safety signs, structural health monitoring, sports equipment and other fields.

CN119331607BActive Publication Date: 2025-10-14SHENZHEN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411236810.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-10-14
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

The stress luminescence brightness and photoluminescence brightness of existing strontium aluminate phosphors are insufficient, and when dopants increase the luminescence intensity, the material structure may become unstable and the luminescence position may shift.

Method used

A luminescent material with the general chemical formula of SrAl2O4:m%Eu-n%Dy-z%B4C is used. By doping Eu and Dy into strontium aluminate and adding B4C, the material is prepared by high-temperature calcination to enhance stress luminescence and photoluminescence.

Benefits of technology

The stress luminescence and photoluminescence properties of strontium aluminate materials have been significantly improved, with high brightness, high sensitivity, and fast response to force, meeting the needs of safety signs, structural health monitoring, and sports equipment without changing the luminescence position.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331607B_ABST
    Figure CN119331607B_ABST
Patent Text Reader

Abstract

The application provides a luminescent material for enhancing stress luminescence and photoluminescence of SrAl2O4 and a preparation method thereof.The chemical general formula of the luminescent material is SrAl2O4:m%Eu-n%Dy-z%B4C;0.001<=m<=10;0.001<=n<=10;0.125<=z<=5;m, n and z represent the molar percentage content.By introducing B4C inorganic compounds and regulating the concentration of the doped B4C, the stress luminescence and photoluminescence performance of the SrAl2O4-based luminescent material is enhanced, and the luminescent material has great potential for commercial application value of strontium aluminate material.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of inorganic luminescent materials, and particularly relates to a luminescent material for enhancing stress luminescence and photoluminescence of SrAl2O4 and a preparation method thereof. BACKGROUND

[0002] Strontium aluminate (SrAl2O4) is an inorganic fluorescent material with excellent optical properties, widely used in luminescence, stress luminescence and other optoelectronic material fields. Its basic chemical formula is SrAl2O4, and it is often doped with rare earth elements such as Eu 2+ and Dy 3+ to significantly improve its luminescent performance. Strontium aluminate has a significant long afterglow effect, that is, it can continue to emit light for several hours even after the light source is turned off, with superior luminous brightness and long light persistence.

[0003] Due to the long afterglow characteristics of strontium aluminate, it has mature commercial applications in the following fields; lighting field: strontium aluminate fluorescent powder is widely used in fluorescent lamps, which can efficiently convert ultraviolet light into visible light; strontium aluminate fluorescent powder can also be used as a laser medium for solid-state lasers to provide efficient laser output. Safety signs and emergency indication field: strontium aluminate can be made into emergency evacuation signs, fire equipment signs, traffic signs, etc., which can provide good visibility even in the case of power failure or low light at night. Decorative field: strontium aluminate can also be used to manufacture various decorations, such as glow-in-the-dark stickers, light-emitting toys and glow-in-the-dark watches. Sports equipment field: strontium aluminate can be used to make glow-in-the-dark sports shoes, sports clothing, etc., to enhance the visibility of night sports and improve the safety of night travel.

[0004] Although strontium aluminate is well known for its long afterglow characteristics, its stress luminescence characteristics have also received widespread attention in recent years, making its application prospect and development space more extensive. Stress luminescence (Mechanoluminescence, ML for short) is a phenomenon of dynamic optical response of materials under the action of mechanical forces such as tension, compression, bending and friction. Compared with traditional electroluminescence, photoluminescence and chemiluminescence, stress luminescence can directly convert mechanical energy into light energy, which is a new type of luminescence.

[0005] Current research on the stress luminescence characteristics of strontium aluminate includes: Japan Institute of Industrial Technology reported that a ML sensor was composed of SrAl2O4:Eu 2+ (SAOE) powder and epoxy resin, which visualized the dynamic strain distribution and fracture phenomenon of carbon fiber reinforced plastic composites in tensile testing. The Institute of Chemistry and Physics of Lanzhou reported the use of SrAl2O4:Eu 2+ ,Dy 3+Composites of surface-adapted artificial dentistry (SAOED) and commercial denture base resin (DBR) allow for direct observation of ML in a standard oral model. Occlusal mechanics can be assessed during artificial occlusal examinations, guiding clinicians to purposefully manipulate the occlusal surface and achieve occlusal balance. Kyungpook National University reported developing an integrated system that combines a SAOED-based ML module to detect the exact location of crack tips and introduces a plastic stress intensity factor (PSIF) to assess the severity of existing cracks. The system also includes dual artificial intelligence modules: a generative adversarial network (GAN) and a convolutional neural network (CNN), as well as finite element method (FEM) simulations, providing reference PSIF results for comparative verification. This system enables on-site structural health monitoring and immediate verification. A team of applicants from Shenzhen University reported fabricating ML speed bumps using SAOED composites. When vehicles pass over them, a bright glowing trail appears, and the long afterglow of the SAOED provides a good warning. The team also composited SAOED powder with PDMS to create a new type of artificial green turf that produces a bright afterglow that slowly decays when pressed with fingers or feet. Applicants from Shenzhen University have also reported leveraging the properties of stress-luminescent materials like strontium aluminate in a variety of products, resulting in numerous patent applications. These include invention patent CN202010928312.4 for a stress-luminescent carpet and its preparation method, and invention patent CN202110774482.6 for a composite lawn and sermon based on sensitive stress-luminescent materials and their preparation method. These patented products require no external power source, emit light upon exposure to pressure, are safe and environmentally friendly, and can visualize a person's walking trajectory. This demonstrates the broad potential and promising applications of strontium aluminate's stress-luminescent properties.

[0006] According to a Business Research report, the global fluorescent pigment market was valued at $380 million in 2023 and is projected to reach $870 million by 2032, with a compound annual growth rate of 9.5% over the forecast period. Strontium aluminate fluorescent materials account for a significant share of this market. Furthermore, strontium aluminate's stress-induced luminescence properties are gaining increasing attention, and its application prospects are expected to expand further, leading to a corresponding increase in market value.

[0007] Although strontium aluminate has a broad industrial base as a mature commercial phosphor, with the advancement of science and technology and the increase in application demand, SAOED materials have also exposed some shortcomings: people have always had a demand for stronger luminous brightness. Higher luminous brightness can enhance the recognition and visibility of strontium aluminate materials, and meet the needs of fields such as high-precision stress measurement and monitoring, thereby broadening its scope of application. Although methods such as adding doping chemicals can improve the luminous brightness of materials to a certain extent, excessive dopants may cause problems such as unstable material structure and luminous position offset. Currently, there are many manufacturers producing strontium aluminate. Improving the luminescent performance of strontium aluminate can help it stand out in the fierce market competition, and research and development of strontium aluminate materials can also promote the increase of its market value.

[0008] In summary, the problems existing in the prior art are: phosphor SrAl2O4:Eu 2+ ,Dy 3+ Stronger stress luminescence brightness and photoluminescence brightness are needed to meet the growing market demand. While adding dopants to enhance the luminescence intensity, it will not cause structural instability of the strontium aluminate material and displacement of the luminescence position. Summary of the Invention

[0009] In order to improve the stress luminescence and photoluminescence properties of strontium aluminate phosphor without changing its luminescence position, the present invention provides a luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence. The chemical formula of the luminescent material is: SrAl2O4:m%Eu-n%Dy-z%B4C, wherein m%Eu represents the molar percentage of Eu doping in SrAl2O4:m%Eu-n%Dy, n%Dy represents the molar percentage of Dy doping in SrAl2O4:m%Eu-n%Dy, and z%B4C represents the molar percentage of B4C doping in SrAl2O4:m%Eu-n%Dy.

[0010] Among them, 0.001≤m≤10, 0.001≤n≤10, 0.125≤z≤5.

[0011] Another object of the present invention is to provide a method for preparing the aforementioned SrAl2O4-based stress-enhanced luminescence and photoluminescence luminescent material, comprising the following steps:

[0012] S1. Weighing raw materials according to the stoichiometric ratio of each element in the chemical formula of the luminescent material, placing the raw materials in a container, adding water and / or an organic solvent into the container, and mixing to obtain a mixed raw material;

[0013] S2, removing water and / or organic solvent from the mixed raw materials and separating to obtain a solid component; placing the solid component in a reducing gas and calcining it at a temperature greater than or equal to 1000° C.;

[0014] S3. Take out the calcined sample to obtain a luminescent material that enhances SrAl2O4-based stress luminescence and photoluminescence.

[0015] Preferably, the raw material corresponding to Sr or Al includes at least one of oxides, hydroxides, chlorides, carbonates, and nitrates corresponding to Sr or Al;

[0016] The raw materials corresponding to Eu or Dy include at least one of the oxides, chlorides, carbonates, and nitrates corresponding to Eu or Dy;

[0017] The raw material corresponding to B4C is B4C.

[0018] Preferably, the reducing gas comprises nitrogen and hydrogen or comprises argon and hydrogen;

[0019] The volume fraction of hydrogen in the reducing gas is 2-20%, and the rest is nitrogen or argon.

[0020] Preferably, the solid component is placed in a reducing gas and calcined at a temperature greater than or equal to 1000° C. as follows:

[0021] The solid component is placed in a reducing gas, heated from room temperature to 1000-1600° C. at a rate of 1-20° C. / min, and kept heated for 1-12 hours.

[0022] Preferably, the organic solvent includes at least one of anhydrous ethanol and isopropyl alcohol.

[0023] Preferably, water and / or organic solvent are removed from the mixed raw materials, and drying treatment is performed to separate and obtain solid components; the drying includes at least one of hot air drying and vacuum drying.

[0024] Preferably, the equipment for heat-insulating and calcining the solid component includes any one of a rotary kiln, a high-temperature reduction furnace, and a muffle furnace.

[0025] Preferably, the calcined sample is taken out, crushed and sieved to obtain a luminescent material that enhances SrAl2O4-based stress luminescence and photoluminescence; wherein the crushing equipment includes any one of a ball mill and a hammer mill, and the screening equipment includes any one of a vibrating screen and a screen.

[0026] Preferably, the container includes any one of a mortar, a blender, and a ball mill.

[0027] The luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0028] The luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence of the present invention has a chemical formula of: SrAl2O4:m%Eu-n%Dy-z%B4C, 0.001≤m≤10, 0.001≤n≤10, 0.125≤z≤5, and SrAl2O4:Eu without B4C 2 + ,Dy 3+ Compared to conventional strontium aluminate materials, the addition of B4C significantly improves the stress-induced luminescence and photoluminescence properties of strontium aluminate materials without changing the luminescence position, and the change in brightness can be observed with the naked eye. Compared to conventional strontium aluminate powders, the luminescent material of this invention exhibits higher brightness, higher sensitivity, and faster force response. It is expected to meet the demand for stronger stress-induced luminescence and photoluminescence performance in fields such as safety signs, structural health monitoring, and sports equipment, achieving higher levels of functionality and recognizability, and improving user experience and satisfaction. It is also expected to stand out in the highly competitive market and meet the growing market demand for strontium aluminate fluorescent powders. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 Flowchart of a method for preparing a luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence provided by an embodiment of the present invention;

[0031] Figure 2 This is a stress luminescence spectrum of the stress luminescence material provided in Examples 1 to 7 and Comparative Example 1 of the present invention under an applied stress of 30N;

[0032] Figure 3 The integrated intensity graph is obtained by integrating the 400-750nm band after obtaining the stress luminescence spectra of the stress luminescence materials provided in Examples 1-7 and Comparative Example 1 of the present invention;

[0033] Figure 4 This is an excitation spectrum diagram of the stress luminescent material provided in Examples 1 to 7 and Comparative Example 1 of the present invention at an absorption wavelength of 524 nm;

[0034] Figure 5 This is an emission spectrum of the stress luminescent material provided in Examples 1 to 7 and Comparative Example 1 of the present invention at an excitation wavelength of 363 nm;

[0035] Figure 6The stress luminescent material provided for the Examples 1 to 7 and Comparative Example 1 of the present application was subjected to an emission spectrum measurement at an excitation wavelength of 363 nm, and the integral intensity in the waveband of 400 to 750 nm was selected for integral intensity measurement. DETAILED DESCRIPTION

[0036] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, but not all embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the present application.

[0037] In order to better understand the present application and not to limit the scope of the present application, all the numbers and other numerical values used in the present application to express amount, percentage, and the like, should be understood as being modified by the word "about" in all cases. Therefore, unless specifically stated otherwise, the numerical parameters set forth in the specification and attached claims are approximations. Any numerical value, however, can inherently contain certain errors necessarily resulting from the standard deviation found in the respective testing measurements used in obtaining that numerical value.

[0038] It should be noted that the sequence of the following embodiments is not intended to limit the preferred sequence of the embodiments. In addition, in the description of the present application, the term "comprising" means "including but not limited to". Various embodiments of the present application can exist in a range type; it should be understood that the description in a range type is merely for convenience and brevity, and should not be understood as a hard limitation on the scope of the present application; therefore, it should be considered that the described range has specifically disclosed all possible sub-ranges and single values in the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, and the like, as well as single numbers in the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated in the present application, it means that any cited number (fraction or integer) in the indicated range is included.

[0039] The application provides a luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence, which has a general chemical formula of SrAl2O4:m%Eu-n%Dy-z%B4C, wherein m%Eu represents a doping amount of Eu, which is a molar percentage of SrAl2O4:m%Eu-n%Dy, n%Dy represents a doping amount of Dy, which is a molar percentage of SrAl2O4:m%Eu-n%Dy, and z%B4C represents a doping amount of B4C, which is a molar percentage of SrAl2O4:m%Eu-n%Dy.

[0040] 0.001<=m<=10, 0.001<=n<=10, and 0.125<=z<=5.

[0041] Another object of the application is to provide a preparation method of the luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence.

[0042] S101, raw materials are weighed according to stoichiometric ratios of elements in the general chemical formula of the luminescent material, and are placed in a container, and water and / or an organic solvent are added into the container, and after mixing, mixed raw materials are obtained;

[0043] S102, the water and / or the organic solvent in the mixed raw materials are removed, and solid components are separated and obtained; the solid components are placed in a reducing gas, and are calcined at a temperature greater than or equal to 1000 DEG C;

[0044] S103, a sample after calcination is taken out, and the luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence is obtained.

[0045] Specifically, as shown in the figure, the preparation method of the luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence provided by the application embodiment comprises the following steps: Figure 1

[0046] S101, raw materials are weighed according to stoichiometric ratios of elements in the general chemical formula of the luminescent material, and are placed in a container, and water and / or an organic solvent are added into the container, and after mixing, mixed raw materials are obtained;

[0047] ​S102, removing water and / or organic solvent from the obtained mixed and uniform raw materials, and performing drying, purification and the like as required, so as to separate a solid component; and placing the obtained solid component in a reducing atmosphere, and performing heat preservation calcination at a temperature of 1000℃ or higher;

[0048] S103, taking out the calcined sample, and performing crushing, screening and the like as required, so as to obtain the SrAl2O4-based semiconductor stress luminescent material doped according to the present application.

[0049] In some embodiments, in step S101, the raw materials for preparing strontium aluminate are prepared, wherein Sr, Al are in the form of oxides, hydroxides, chlorides, carbonates, nitrates and the like; Eu, Dy are in the form of oxides, chlorides, carbonates, nitrates and the like, and B4C is an inorganic compound; for example, the raw material corresponding to Sr is SrCO3, the raw material corresponding to Al is Al2O3, the raw material corresponding to Eu is Eu2O3, and the raw material corresponding to Dy is DyCl3.

[0050] In some embodiments, in step S101, the container is only required to have a stirring function capable of mixing the raw materials, and is not particularly limited, for example, a mortar, a stirrer, a ball mill and the like.

[0051] In some embodiments, in step S101, the water and / or organic solvent used for mixing the raw materials are not particularly limited, for example, deionized water, anhydrous ethanol, isopropyl alcohol and the like can be used.

[0052] In some embodiments, in step S102, the drying, purification and the like are not particularly limited, for example, drying can be performed by hot air drying, vacuum drying and the like; and purification can be performed by removing impurities by filtration.

[0053] In some embodiments, in step S102, the mixed raw materials are calcined in a reducing atmosphere, and the reducing atmosphere is not particularly limited, for example, a reducing atmosphere comprising nitrogen and hydrogen or a reducing atmosphere comprising argon and hydrogen can be used, and the volume fraction of nitrogen or argon in the reducing atmosphere is 80-98%, and the corresponding volume fraction of hydrogen is 20-2%.

[0054] In some embodiments, in step S102, the machine for calcining the mixed raw materials is not particularly limited, for example, a rotary kiln, a high-temperature reduction furnace, a muffle furnace and the like can be used; for example, in the case of calcining in a muffle furnace, the calcination is performed by heating from room temperature (25℃) to 1000-1600℃ at a rate of 1-20℃ / min, and then performing heat preservation calcination for 1-12 hours.

[0055] In some embodiments, in step S103, the calcined sample is taken out, and as the content of B4C increases, the color of strontium aluminate gradually changes from light yellow to yellow-green, and the hardness also gradually increases.

[0056] In some embodiments, the machine for crushing and screening in step S103 is not particularly limited, for example, a ball mill, a hammer mill, a vibrating screen, etc. can be used; or it can be manually operated, the sample is crushed in a mortar, and then transferred to a screen for screening.

[0057] The luminescent material prepared by the method can significantly improve the stress luminescence performance and photoluminescence performance of strontium aluminate material, without changing the luminescence position, and the change in brightness can be observed by naked eye.

[0058] The following further illustrates the luminescent material and the preparation method thereof according to the present application with specific examples. This part further illustrates the content of the present application in combination with specific examples, but should not be understood as a limitation of the present application. If not particularly stated, the technical means used in the examples are conventional means known to those skilled in the art. Unless particularly stated, the reagents, methods and equipment used in the present application are conventional reagents, methods and equipment in the art.

[0059] Example 1

[0060] The present embodiment provides a luminescent material for enhancing stress luminescence and photoluminescence of SrAl2O4 base, which has a general chemical formula of SrAl2O4:m%Eu-n%Dy-z%B4C, wherein m%Eu represents the doping amount of Eu as a molar percentage of SrAl2O4:m%Eu-n%Dy, n%Dy represents the doping amount of Dy as a molar percentage of SrAl2O4:m%Eu-n%Dy, and z%B4C represents the doping amount of B4C as a molar percentage of SrAl2O4:m%Eu-n%Dy.

[0061] wherein m = 1, n = 0.05, and z = 0.025;

[0062] The preparation method of the luminescent material for enhancing stress luminescence and photoluminescence of SrAl2O4 base comprises the following steps:

[0063] S101, the raw materials are weighed according to the stoichiometric ratio of each element in the general chemical formula of the luminescent material, specifically, the raw materials are SrCO3, Al2O3, Eu2O3, DyCl3·6H2O and B4C, the molar ratio of SrCO3, Al2O3, Eu2O3, DyCl3·6H2O and B4C is 98.95:100:0.5:0.05:0.025, and the mass of SrCO3, Al2O3, Eu2O3, DyCl3·6H2O and B4C is 14.6080g, 10.1960g, 0.1760g, 0.0188g and 0.0014g, respectively;

[0064] S102, pour the mixed raw materials of the above-mentioned formula into a container, and add 30 ml of anhydrous ethanol into the mixed raw materials, and mix them evenly in the container; remove water and / or organic solvents from the obtained mixed and evenly-mixed raw materials, and perform hot air drying treatment, so as to separate out solid components; place the obtained solid components into a crucible, pass reducing gas containing 95% by volume of nitrogen and 5% by volume of hydrogen, and heat from room temperature to 1000℃ at a heating rate of 10℃ / min, then heat from 1000℃ to 1400℃ at a heating rate of 5℃ / min, and keep the temperature for calcination for 5 hours, and finally naturally cool down with the furnace;

[0065] S103, take out the calcined sample, and perform crushing and sieving operations, so as to obtain the stress luminescent material SrAl2O4:Eu 2+ ,Dy 3+ ,B4C powder, which is a luminescent material for enhancing stress luminescence and photoluminescence of SrAl2O4.

[0066] Examples 2-7

[0067] The preparation method of the luminescent material for enhancing stress luminescence and photoluminescence of SrAl2O4 provided in Examples 2-7 is the same as that in Example 1, except that the molar ratio and the mass of the raw materials used are different. The molar ratio and the mass of the raw materials used in Examples 1-7 are shown in Table 1 below, and the preparation process of Examples 2-7 is the same as that of Example 1.

[0068] Table 1 - Molar ratio and mass of raw materials used in Examples 1-7

[0069]

[0070]

[0071] In Examples 2-7, m is 1 and n is 0.05, and the value of z in Examples 2-7 is 0.125, 0.25, 0.5, 0.75, 1.25, and 1.75, respectively.

[0072] Comparative Example 1

[0073] This comparative example provides a preparation method of a SrAl2O4:Eu 2+ ,Dy 3+ powder, which is the same as that in Example 1, except that B4C is not added during preparation. The specific preparation method comprises the following steps:

[0074] S101, the raw materials are weighed according to the stoichiometric ratio of each element in the chemical formula of the luminescent material, specifically, the raw materials are SrCO3, Al2O3, Eu2O3, DyCl3·6H2O, and B4C, the molar ratio of SrCO3, Al2O3, Eu2O3, DyCl3·6H2O, and B4C is 98.95:100:0.5:0.05:0, and the mass of SrCO3, Al2O3, Eu2O3, DyCl3·6H2O, and B4C is 14.6080 g, 10.1960 g, 0.1760 g, 0.0188 g, and 0 g (i.e., no B4C is added) respectively;

[0075] S102, the mixed raw materials of the above formula are poured into a container, 30 ml of anhydrous ethanol is added to the mixed raw materials, and the mixed raw materials are fully mixed and uniformly distributed in the container; water and / or organic solvents are removed from the obtained mixed and uniformly distributed raw materials, and hot air drying treatment is performed, so as to separate out solid components; the obtained solid components are placed in a crucible, reducing gas containing 95% by volume of nitrogen and 5% by volume of hydrogen is introduced, the temperature is raised from room temperature to 1000℃ at a temperature raising rate of 10℃ / min, then the temperature is raised from 1000℃ to 1400℃ at a temperature raising rate of 5℃ / min, and the temperature is kept for calcination for 5 hours, and finally the furnace is naturally cooled down;

[0076] S103, the calcined sample is taken out, and crushing and screening operations are performed, so as to obtain SrAl2O4:Eu 2+ ,Dy 3+ powder.

[0077] The molar ratio of the raw materials used in Comparative Example 1 and the mass of the raw materials are shown in Table 2 below.

[0078]

[0079] In the above Tables 1-2, the stress luminescence integral intensity and the photoluminescence integral intensity are the integral intensity data obtained by integrating the emission spectrum of the luminescent material prepared in Examples 1-7 and Comparative Example 1 in the wavelength range of 400-750 nm (i.e., the data of Figure 3 ), and the integral intensity data obtained by integrating the emission spectrum at an excitation wavelength of 363 nm in the wavelength range of 400-750 nm (i.e., the data of Figure 6 ).

[0080] Test analysis

[0081] The strontium aluminate powder material prepared in Examples 1-7 and Comparative Example 1 was weighed into a centrifuge tube, and a small amount of light-cured UV glue was added dropwise, followed by the addition of anhydrous ethanol. After shaking to mix, the mixture was poured into a mold and placed in an oven at 80-100°C to dry the anhydrous ethanol. Then, a plastic sealing machine was used to heat and plasticize to obtain the stress luminescence sheet required for testing, and the stress luminescence performance was tested.

[0082] Specifically, the stress luminescence characteristic test: the prepared stress luminescence sheet was tested using a spectrometer-force meter-sliding motor. First, the prepared stress luminescence test sheet was attached to the self-made stress luminescence test equipment and fixed vertically on the high-transparency acrylic plate, and the pressure applied to the test sheet by the sliding motor was set. Then, the sliding motor was controlled to slide left and right vertically to the sheet. During the sliding process, the light emitted by the stress luminescence sheet was collected by the optical fiber and transmitted to the spectrometer. Finally, the collected stress luminescence material luminous intensity was displayed on the computer. The test results are shown in Figures 2-3 .

[0083] Figure 2 The stress luminescence spectrum of the strontium aluminate luminescent material with different doping ratios of B4C in Examples 1-7 and Comparative Example 1 under a stress of 30N is shown in Figure 2 From the figure, it can be seen that the emission wavelength of the material stress luminescence is about 524nm, and compared with Comparative Example 1, the stress luminescence performance is basically enhanced after adding B4C, and the luminescence position does not change.

[0084] Figure 3 The stress luminescence spectrum of the strontium aluminate luminescent material with different doping ratios of B4C in Examples 1-7 and Comparative Example 1 under a stress of 30N is shown in

[0085] Table 3 shows the growth of the stress luminescence spectrum integral intensity of the luminescent material prepared in Examples 1-7 compared with the stress luminescence spectrum integral intensity of Comparative Example 1.

[0086] Table 3 shows the growth of the stress luminescence spectrum integral intensity of the luminescent material prepared in Examples 1-7 compared with the stress luminescence spectrum integral intensity of Comparative Example 1.

[0087] Example Enhancement ratio Example 1 -26.62% Example 2 17.14% Example 3 86.41% Example 4 258.39% Example 5 349.92% Example 6 255.69% Example 7 188.56%

[0088] The Edinburgh FLS steady-state fluorescence spectrometer was used to test the strontium aluminate luminescent material with different doping ratios of B4C prepared in Examples 1-7 and Comparative Example 1, and the excitation spectrum and emission spectrum were obtained. The test results are shown in Figures 4-6 .

[0089] Figure 4The excitation spectra of strontium aluminate luminescent materials with different doping ratios of B4C prepared in Examples 1 to 7 of the present invention and Comparative Example 1 at an absorption wavelength of 524 nm are shown; Figure 5 Emission spectra of strontium aluminate luminescent materials with different doping ratios of B4C prepared in Examples 1 to 7 of the present invention and Comparative Example 1 at an excitation wavelength of 363 nm. Compared with Comparative Example 1, the addition of B4C enhances the photoluminescence performance while maintaining the same emission position. Figure 6 The emission spectra of the strontium aluminate luminescent materials with different B4C doping ratios prepared in Examples 1 to 7 of the present invention and Comparative Example 1 at an excitation wavelength of 363 nm are plotted, and the integrated intensity graph is obtained by integrating the 400-750 nm band. By comparison, it can be seen that the photoluminescence intensity of Comparative Example 1 (SAOED without B4C doping) is the lowest, and the photoluminescence intensities of the other strontium aluminate powders doped with B4C are all stronger than that of Comparative Example 1. Among them, the photoluminescence intensity of Example 5 (SAOED doped with 0.75% B4C) is the highest, which is approximately 22.35% of that of Comparative Example 1, as shown in Table 4.

[0090] Table 4 shows the growth of the integrated intensity of the photoluminescence emission spectra of the luminescent materials prepared in Examples 1 to 7 compared with that of Comparative Example 1.

[0091] Table 4 - Growth of the integrated intensity of the photoluminescence emission spectra of the luminescent materials prepared in Examples 1 to 7

[0092] Example Enhancement ratio Example 1 6.68% Example 2 2.03% Example 3 19.43% Example 4 15.6% Example 5 22.35% Example 6 15.04% Example 7 13.55%

[0093] The above test results demonstrate that the overall stress luminescence intensity and photoluminescence intensity of the B4C-doped strontium aluminate powder prepared in the present invention are significantly enhanced compared to undoped strontium aluminate powder, that is, compared to Comparative Example 1. The stress luminescence intensity of the luminescent material prepared in Example 5, which is the best example, is approximately 3.5 times stronger than that of Comparative Example 1, meeting the stress luminescence intensity requirements for structural health monitoring, transportation facilities, sports equipment, and other fields. Furthermore, the photoluminescence intensity of the luminescent material prepared in Example 5, which is the best example, is 22.35% stronger than that of Comparative Example 1, effectively meeting market demand for photoluminescence intensity in strontium aluminate phosphors. Overall, B4C-doped strontium aluminate powder demonstrates strong market competitiveness.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence, characterized in that: The general chemical formula of the luminescent material is: SrAl2O4:m%Eu-n%Dy-z%B4C, wherein m%Eu represents the molar percentage of Eu doping in SrAl2O4:m%Eu-n%Dy, n%Dy represents the molar percentage of Dy doping in SrAl2O4:m%Eu-n%Dy, and z%B4C represents the molar percentage of B4C doping in SrAl2O4:m%Eu-n%Dy. Wherein, m=1, n=0.05, 0.125≤z≤1.75; The method for preparing the luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence comprises the following steps: S1. Weighing raw materials according to the stoichiometric ratio of each element in the chemical formula of the luminescent material, placing the raw materials in a container, adding water and / or an organic solvent into the container, and mixing to obtain a mixed raw material; S2, removing water and / or organic solvent from the mixed raw materials and separating to obtain a solid component; placing the solid component in a reducing gas and calcining it at a temperature greater than or equal to 1000° C.; S3, taking out the calcined sample, thus obtaining a luminescent material having enhanced SrAl2O4-based stress luminescence and photoluminescence; The reducing gas includes nitrogen and hydrogen or argon and hydrogen; The volume fraction of hydrogen in the reducing gas is 2 to 20%, and the rest is nitrogen or argon; The solid component is placed in a reducing gas and calcined at a temperature greater than or equal to 1000°C. Specifically: The solid component was placed in a reducing gas, heated from room temperature to 1000°C at a heating rate of 10°C / min, then heated from 1000°C to 1400°C at a heating rate of 5°C / min, and calcined for 5 hours.

2. A method for preparing a luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence according to claim 1, characterized in that: The following steps are involved: S1. Weighing raw materials according to the stoichiometric ratio of each element in the chemical formula of the luminescent material, placing the raw materials in a container, adding water and / or an organic solvent into the container, and mixing to obtain a mixed raw material; S2, removing water and / or organic solvent from the mixed raw materials and separating to obtain a solid component; placing the solid component in a reducing gas and calcining it at a temperature greater than or equal to 1000° C.; S3, taking out the calcined sample, thus obtaining a luminescent material having enhanced SrAl2O4-based stress luminescence and photoluminescence; The reducing gas includes nitrogen and hydrogen or argon and hydrogen; The volume fraction of hydrogen in the reducing gas is 2 to 20%, and the rest is nitrogen or argon; The solid component is placed in a reducing gas and calcined at a temperature greater than or equal to 1000°C. Specifically: The solid component was placed in a reducing gas, heated from room temperature to 1400°C at a rate of 10°C / min, and calcined for 5 hours.

3. The method for preparing a luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence according to claim 2, characterized in that: The raw material corresponding to Sr or Al includes at least one of oxides, hydroxides, chlorides, carbonates, and nitrates corresponding to Sr or Al; The raw materials corresponding to Eu or Dy include at least one of the oxides, chlorides, carbonates, and nitrates corresponding to Eu or Dy; The raw material corresponding to B4C is B4C.

4. The method for preparing a luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence according to claim 2, wherein: The organic solvent includes at least one of anhydrous ethanol and isopropyl alcohol.

5. The method for preparing a luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence according to claim 2, wherein: The water and / or organic solvent in the mixed raw materials are removed, and drying treatment is performed to separate and obtain a solid component; the drying includes at least one of hot air drying and vacuum drying.

6. The method for preparing a luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence according to claim 2, wherein: The equipment for heat-insulating and calcining the solid components includes any one of a rotary kiln, a high-temperature reduction furnace, and a muffle furnace.

7. The method for preparing a luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence according to claim 2, wherein: The calcined sample is taken out, crushed and sieved to obtain a luminescent material that enhances SrAl2O4-based stress luminescence and photoluminescence; wherein the crushing equipment includes any one of a ball mill and a hammer mill, and the screening equipment includes any one of a vibrating screen and a screen.

8. The method for preparing a luminescent material for enhancing SrAl2O4-based stress luminescence and photoluminescence according to claim 2, wherein: The container includes any one of a mortar, a blender, and a ball mill.

Citation Information

Patent Citations

  • Stress light-emitting carpet and preparation method thereof

    CN112143073A

  • Composite lawn and cloth channel based on sensitive stress luminescent material and preparation method of composite lawn and cloth channel

    CN113604902A

  • Phosphorescence phosphor composite and manufacturing method thereof

    KR1020140138408A